Evaluasi Kinerja Program Gerakan Pembangunan Masyarakat Adil Sejahtera GERBANGMAS dalam Pemberdayaan Masyarakat Kampung Mandiri untuk Meningkatkan Kesejahteraan Sosial di Kabupaten Mahakam Ulu - Servinus Manek Bria; Sri Roekminiati; Sri Kamariyah; Ika Devy Pramudiana (Journal of Innovative and Creativity, 2025)
This study aims to evaluate the performance of the Gerakan Pembangunan Masyarakat Adil Sejahtera (GERBANGMAS) Program in empowering the Kampung Mandiri community to improve social welfare in Mahakam Ulu Regency. This program is designed to provide assistance in the form of training, capital for businesses, and access to basic services to improve the community's living standards. The method used in this study is a qualitative approach, with data collection techniques including in-depth interviews, field observations, and document studies. The findings show that the effectiveness of the GERBANGMAS program is measured at around 75%, successfully improving social welfare, although there is an unequal distribution of benefits between more active groups and less organized ones. The program’s efficiency is recorded at 70%, indicating resource wastage, particularly in the management of funds and the distribution of assistance that is not accurately targeted. The sufficiency of the program is recorded at 80%, but there are gaps in business mentoring and long-term business development. The conclusion of this study is that although the GERBANGMAS Program has had a positive impact, several areas need improvement to increase its overall impact. Recommendations include enhancing efficiency in resource management, adjusting assistance to better meet the long-term needs of the community, and improving the distribution of benefits to ensure it is more evenly spread across all community groups. Additionally, there is a need to provide more relevant training and continuous mentoring to optimize the program’s success.